Сreative industry 4.0: trends and transformations in the era of digitalization - Iryna Shkodina; Natalya Kondratenko; Anastasia Shchukina (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
In the contemporary world, creativity has emerged as a pivotal factor in the development of international economic relations. This article explores the development of the global creative industry 4.0, shaped by the fourth industrial revolution (Industry 4.0). The study aims to examine the trends influencing the creative industries, molded by the intensification of digitization, fostering fundamental changes and transforming them into the creative industry 4.0. The research employs a combination of general scientific and specialized methods, including a systemic approach to justify the main trends in the transformation of creative industries, analysis and synthesis to identify the impact of digital technologies on their evolution, and expert assessment methods to develop approaches for enhancing the development of creative industries 4.0. Results indicate that the digitization of the creative economy has expanded its scale and societal impact. Creative industries are becoming digital not only in terms of services but also in the realm of products. Artificial intelligence, virtual reality, big data, and other digital technologies facilitate the production, scaling, and consumption of creative services and products. The application of digital technologies enhances production efficiency, unlocks unlimited creative potential, improves design, personalization, interactivity, and consumer properties of creative goods and services. The trend of merging entertainment with e-commerce is expected to intensify. The development of the creative economy is crucial for achieving sustainable development goals, stimulating small business growth, and creating new employment opportunities, especially for women, youth, and other vulnerable population groups. The article identifies how Industry 4.0 technologies transform creative industries and proposes ways to leverage these new technological trends for the economic recovery of Ukraine.